Correctly Identifying Deaths Due to Drug Toxicity Without a Forensic Autopsy. (June 2019) - Dye, Daniel W.; McGwin, Gerald; Atherton, Daniel S.; McCleskey, Brandi; Davis, Gregory G.
Abstract : Abstract: In 2005, the National Association of Medical Examiners approved the Forensic Autopsy Performance Standards. Standard B3.7 indicates that a forensic pathologist shall perform a forensic autopsy when the death is by apparent intoxication by alcohol, drugs, or poison. The Jefferson County Coroner/Medical Examiner Office has observed an increase in our caseload by 10% per year since 2012. We designed a study to determine if a pathologist could correctly classify the cause of death (COD) and manner of death (MOD) of suspected drug-related deaths without information from the internal examination. The determination of the COD and MOD was then compared with the case file, which includes information from the internal examination and microscopy, to determine agreement between the case file and the reclassification. The percent correct for COD and MOD was calculated, and kappa values were calculated for MOD. The pathologists were able to correctly classify the COD in 73% of cases. For MOD, 2 pathologists achieved substantial agreement between the test cases and the actual case file. The third pathologist had moderate agreement. These findings indicate that a full postmortem examination is necessary to correctly classify the COD/MOD in cases of suspected drug toxicity. Our null hypothesis is that a full autopsy is not necessary to correctly classify the COD and MOD in cases of drug toxicity.